Design and Development Methodology of ‘Komputer Saya’: Multimedia Courseware for Slow Learners - Abdollah, Norfarhana; Wan Ahmad, Wan Fatimah; Patah Akhir, Emelia Akashah (2010)
Multimedia technology have been proven as an effective tool in education and implemented for its advantages and capabilities. The nature of multimedia itself which consists of combinations of media elements that can promote multi-sensory learning can facilitate slow learners in their learning. The aim of this research is to develop a multimedia courseware for slow learners in order to assist and increase their motivation in learning. The courseware namely ‘Komputer Saya’ consists of learning theme of multimedia, as referring to the Special Education Syllabus for Learning Disabled. This paper discusses on several issues; firstly on the slow learners’ definition, characteristics, suitable instructional guideline that can be applied in the courseware. Secondly, the research methodology that adapts IntView courseware development methodology for design and development phases will be discussed. The final part contains the output of design and development phases which are the courseware navigational structure and some screenshots of the courseware pages. The development of the ‘Komputer Saya’ courseware is believed could offer many advantages to the slow learners during their lessons.